A revised and updated checklist of Monogononta rotifers from Argentina - Ferrando, Noelia Soledad (2016)
We provide here a checklist of species of Monogononta rotifers from lentic and lotic environments in Argentina, 25 years after the initial catalogue compiled by Susana B. José de Paggi. This new inventory now includes the reports on rotifers documented in 93 studies produced after 1990. The majority of the investigations were carried out in three of the 24 Argentine provinces. In addition, the presence of 13 species in samples from three water bodies within Buenos Aires province are now cited here for the first time in Argentina. In this updated checklist, a total of 351 species are catalogued, the majority being representatives of the Lecanidae, Brachionidae, and Lepadellidae.